ANALISIS ILOKUSI UNTUK KATA “LO” DAN “GUE” DALAM PERNYATAAN MAHALINI PADA PODCAST RADITYA DIKA - Zikrilla Qolbi Elok; Nawal Nuha Yoman; Awindha Khoirusyifa (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2026)
This research investigates the illocutionary acts used by Mahalini Raharja during her conversation with Raditya Dika on his YouTube podcast, with particular attention to utterances containing the informal pronouns “lo” and “gue.” The purpose of this study is to determine the types of illocutionary acts expressed through these utterances and to explore how communicative intentions are conveyed in an informal podcast interaction. The study applies a qualitative descriptive method and employs Searle’s theory of illocutionary acts as the main analytical framework. The data consisted of 38 utterances containing the pronouns “lo” and “gue,” which were transcribed and analyzed according to their pragmatic functions. The results show that four categories of illocutionary acts were identified: assertive, expressive, directive, and commissive acts. Among these categories, assertive acts appeared most frequently, representing 68.4% of the data, followed by expressive acts at 26.3%, while directive and commissive acts were found only once each. Declarative acts were not identified in the analysis. The findings indicate that assertive and expressive acts dominate the interaction because podcast conversations commonly emphasize storytelling, personal experiences, and emotional expression. In conclusion, the pronouns “lo” and “gue” serve not only as indicators of casual language, but also as pragmatic tools that help speakers perform communicative intentions and construct meaning in digital conversational contexts. Keywords: pragmatics, illocutionary acts, podcast interaction, speech act analysis, informal pronouns